TRANSFORMATIONAL PROCESSES BETWEEN THE SETTLERS AND THE LOCAL POPULATION IN TURKESTAN DURING THE SECOND HALF OF THE 19TH CENTURY AND THE EARLY 20TH CENTURY - Temirova, Sh.V. (Oriental Journal of History, Politics and Law, 2025)
This article analyzes the empire-wide and local legal-normative documents aimed at the policy of population relocation to Turkestan in the second half of the 19th century - the beginning of the 20th century of the Russian Empire went.